2016
DOI: 10.1111/ejss.12381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil and climatic factors on arbuscular mycorrhizal fungi in rhizosphere soil underRobinia pseudoacaciain theLoessPlateau,China

Abstract: We explored arbuscular mycorrhizal fungi (AMF) in the rhizosphere soil under Robinia pseudoacacia L., Leguminosae (black locust), and evaluated the relations between their diversity and soil and climatic factors in the semi‐arid Loess Plateau of northwest China. A total of 23 AMF species were identified at six sites. Of these, six belonged to the genus Funneliformis (Glomeraceae), five to Rhizophagus (Glomeraceae), three to Glomus (Glomeraceae), two to Acaulospora (Acaulosporaceae), two to Claroideoglomus (Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…In this study, the high spore density and mycorrhizal colonization rate indicated that well-established mutualistic symbioses exist between AM fungi and the dominant tree species found on the Loess Plateau. Mutualistic relationships have been reported before for AM fungi with R. pseudoacacia [9,13], H. rhamnoides [10], P. cathayana [42], and J. communis [43], but not yet for S. matsudana. Many studies have demonstrated that AM fungi protect their host plants against the adverse effects of drought stress and soil nutrient depletion [3,9].…”
Section: Discussionmentioning
confidence: 79%
“…In this study, the high spore density and mycorrhizal colonization rate indicated that well-established mutualistic symbioses exist between AM fungi and the dominant tree species found on the Loess Plateau. Mutualistic relationships have been reported before for AM fungi with R. pseudoacacia [9,13], H. rhamnoides [10], P. cathayana [42], and J. communis [43], but not yet for S. matsudana. Many studies have demonstrated that AM fungi protect their host plants against the adverse effects of drought stress and soil nutrient depletion [3,9].…”
Section: Discussionmentioning
confidence: 79%
“…The AM fungi of the phylum Glomeromycota have existed for over 460 million years (Khan, 2005). The mutualistic symbiosis between AM fungi and plants is ubiquitous (He et al, 2016; Murugesan et al, 2016). In natural conditions, AM fungi are associated with at least 80% of terrestrial plants, including pteridophytes, gymnosperms, and angiosperms (Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to [33] the diversity and density of AMF spores in the soil are determined by the activity of the previous crop cultivation. Moreover, according to [34], the precipitation may also have a direct impact on the diversity and population of AMF.…”
Section: A the Type Numbers And Frequency Of Sporesmentioning
confidence: 99%